VOLUME INCREMENT OF Nectandra megapotamica (Spreng.) MEZ ON A MIXED RAIN FOREST - Souza, Luis Henrique da Silva (2009)
In this work, it is studied the growth of Nectandra megapotamica (Spreng.) Mez species through a sampler compounded by eleven dominant trees selected from a rainforest in Nova Prata, Rio Grande do Sul. The mathematical model which better represents the growth trend in percentage volume was described as iv%=(b0+b1.ln d)2, fitting individually per tree, being possible to describe the variations of slope (b1) and intercept (b0) coefficients between trees with the relation height – diameter (h/d), diameter increment measured on the last 5 cm on bore increment (id5) sampled on diameter breast height (d), exposition (EXPOS), corrected Basal Area Large (BALcor) and crown length exposed to sunlight (Lc), considering the following expressions: b1= 0,41739 + 4,16179.id5 - 6,29332.h/d + 0,37823.EXPOS - 0,11519Ir + 5,80419.BALcor – 0,06858.Lc, with determination coefficient equal to 0,9979 and standard error in percentage of the mean of –1,73%, and b0= 2,62466 –13,37024.id5 + 22,08329.h/d – 1,33161.EXPOS + 0,34689.Ir –23,88899.BALcor + 0,25692.L, with determination coefficient fitting on 0,9907 and standard error in percentage of the mean of 2,71%.